Anti Ulcer Activity Of Curcuma Longa Against Indomethacin Induced Gastric Ulcers In Albino Rats - Nagle, R.; Shrman, K.; Sharma , R. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
In the present study, anti ulcer activity of Curcuma longa was evaluated against Indomethacine induced gastric ulcers in rats. The ulcers were produced by oral administration of indomethacin @ 15 mg/kg b.w. The extract of C. longa was given @ 600 mg/kg b.w. by oral route to the experimental albino rats. Ranitidine was used as standard drug. Alcoholic extract of C. longa significantly reduce the number and severity of the gastric ulcers by lowering ulcer index and ulcer score and increasing healing index indicating the ulcer protective action of C.longa.